FAKTOR - FAKTOR YANG BERHUBUNGAN DENGAN KEPUASAN PEMANFAATAN PENOLONG PERSALINAN PADA IBU BERSALIN DI RUMAH SAKIT GRANDMED LUBUK PAKAM - Basyariah Lubis; Sri Melda Br.Bangun (JURNAL KEBIDANAN KESTRA (JKK), 2019)
Factors causing high MMR (Maternal Mortality Rate) is highly diverse, among others, is the delay in deciding to seek immediate treatment / assistance, the behavior of people who do not recognize the danger signs and not aware of the existence of complications. Patient satisfaction with the use of birth attendant became one of the main components or most important. Thus, patient satisfaction is one of the goals of improving the quality of health services. In improving the management of service quality complaints / complaint of patients is needed. Until now there are still some complaints (one of which is the lack of attention of the birth attendant) of the patients and families of patients received by the hospital, either directly or indirectly. This type of research is a survey with cross sectional design. Analytical survey method used to determine the factors associated with utilization of satisfaction birth attendants in the Hospital Grand Medistra Lubukpakam The population in this study were women giving birth in hospitals Grand Medistra Lubukpakam with a sample of 73 people. The study was conducted in September s / d in October 2015. The data was obtained using a questionnaire and analyzed using multiple logistic regression test at the level of 95%. Multivariate analysis with multiple logistic regression test showed that the variables of knowledge has the most impact on satisfaction utilization birth attendants, namely in terms of the value of B = 5.041 (95% CI 1.262; 20.129), which means that the knowledge variable has the effect of five (5) times to satisfaction utilization birth attendant. For doctors and midwives Hospital Grand Medistra which helped birth is expected to further improve service to patients with more empathy for patients, providing sufficient time and be more patient to accompany a patient who was in labor, building a good relationship with the patient's family so can further improve the satisfaction in the utilization of birth attendant.